2018
DOI: 10.1093/gbe/evy106
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomic Analysis of Lactobacillus curvatus Reveals Two Lineages Distinguished by Genes for Fermenting Plant-Derived Carbohydrates

Abstract: Lactobacillus curvatus is a lactic acid bacterium encountered in many different types of fermented food (meat, seafood, vegetables, and cereals). Although this species plays an important role in the preservation of these foods, few attempts have been made to assess its genomic diversity. This study uses comparative analyses of 13 published genomes (complete or draft) to better understand the evolutionary processes acting on the genome of this species. Phylogenomic analysis, based on a coalescent model of evolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 59 publications
1
23
0
1
Order By: Relevance
“…Teran et al [ 26 ] conducted a comparative analysis of 13 published genomes ( L. curvatus NRIC0822, Wikim 38, FBA2, DSM20019, Wikim 52, CRL705, RI-193, RI-198, RI-124, KG6, FLEC03, RI-406, MRS6) and found that the L. curvatus core genome contains 6742 sites of single nucleotide polymorphism, which can be used to distinguish two major lineages. Lineage one is represented by the newly sequenced strain, L. curvatus FLEC03, and lineage two contains two branches, with branch 2A represented by the type-strain L. curvatus DSM20019 and branch 2B represented by L. curvatus KG6.…”
Section: Genomic Characteristics Of Latilactobacillus Cumentioning
confidence: 99%
See 2 more Smart Citations
“…Teran et al [ 26 ] conducted a comparative analysis of 13 published genomes ( L. curvatus NRIC0822, Wikim 38, FBA2, DSM20019, Wikim 52, CRL705, RI-193, RI-198, RI-124, KG6, FLEC03, RI-406, MRS6) and found that the L. curvatus core genome contains 6742 sites of single nucleotide polymorphism, which can be used to distinguish two major lineages. Lineage one is represented by the newly sequenced strain, L. curvatus FLEC03, and lineage two contains two branches, with branch 2A represented by the type-strain L. curvatus DSM20019 and branch 2B represented by L. curvatus KG6.…”
Section: Genomic Characteristics Of Latilactobacillus Cumentioning
confidence: 99%
“…The ability to metabolize carbohydrates is an important indicator for the cultivation and selection of bacteria. Teran et al [ 26 ] analyzed the L. curvatus genome and found multiple carbohydrate uptake systems ( Figure 2 ). They found that L. curvatus has at least three pathways to utilize maltose.…”
Section: Physiological and Biochemical Properties Of Latmentioning
confidence: 99%
See 1 more Smart Citation
“…Lactobacillus curvatus is a facultative heterofermentative LAB traditionally associated with fermented meat products, vacuum-packaged refrigerated meat, poultry, and fish products [15]. This species is ubiquitous as it was also isolated from other ecological niches, such as fermented vegetables and dairy products [16][17][18]. To date, the sequences of 19 L. curvatus plasmids, with sizes ranging from 2 kb to 61 kb, have been uploaded in the NCBI database.…”
Section: Introductionmentioning
confidence: 99%
“…curvatus , which are closely related to Lactobacillus sakei (7), is detected in a variety of resources including fermented foods and animal intestine, and Lb. curvatus has shown genomic diversity (8, 9). Our present analyses identified three Lb.…”
mentioning
confidence: 99%